'"Dare you meet a woman": black women, abolitionism, and protective violence, 1850–1859'. (3rd April 2021) - Jackson, Kellie Carter
ABSTRACT: 'Dare you Meet a Woman' examines how black women exhibited their willingness to take on forceful and even violent action to dismantle the institution of slavery. Black resistance was central to abolitionism and black women were essential to the movement. This essay argues that their activism should be examined as the politics of protective violence . The politics of protective violence explains black women's employment of force to protect themselves and their communities and ultimately promote the overthrow of slavery. Beginning with the Christiana Resistance in 1851 and culminating with John Brown's raid on Harpers Ferry, this essay examines the bookends and high points of free and fugitive black women's responses during key turning points of the 1850s. In sum, black women violently resisted the Fugitive Slave Law and anti-black oppression. Moreover, black women leaders contributed significantly to the acceleration of violent sectional tensions and, ultimately, the American Civil War.